PENGARUH KEPUTUSAN INVESTASI,PENDANAAN, KEBIJAKAN DIVIDEN, DAN MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN - Eveline, Debby Gabriella; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Maximizing firm value is one of company priorities in running its operations. Firm value which is reflected in share price is one of important elements for investors who want to invest their capital. This research is meant to examine the influence of investment decision, funding decision, dividend policy, intellectual capital to firm value of manufacturing companies which are listed in Indonesia Stock Exchange (IDX).The population has been obtained by using purposive sampling method to the manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2014 periods and they have been selected based on the determined criteria so manufacturing companies have been obtained as samples. The analysis method has been carried out by using multiple linear regressions analysis and the SPSS application. The result of goodness of fit test shows that investment decision, funding decision, and dividend policy is the explanatory factor of firm value. The result of hypothesis test which has been done by using t test shows that funding decision and intellectual capital has an influence to the firm value 000 whereas investment decision and dividen policy does not have any influence to the firm value. Keywords: Investment decision, funding decision, dividend policy, intellectual capital.